40 Tahun penyelidikan Fakulti Pengajian Islam Universiti Kebangsaan Malaysia. - Ahmad Sunawari Long; Zaizul Abdul Rahman (Universiti Kebangsaan Malaysia, 2012)
Since its establishment on May 18, 1970, various researches on Islam and Muslim communities were conducted by researchers of Faculty of Islamic Studies. Various grants are channelled to the researchers, including IRPA grant, (The Intensification of Research in Priority Areas), FRGS Grant (Fundamental Research Grant Scheme), Grant from government agencies such as the Department of Islamic Development Malaysia (JAKIM) and the Ministry of Education, University Research Grant (GUP), Action/Strategic Research Grant, Arus Perdana Grant, Laluan Pantas Grant and Incentive Grant Funds. Since its establishment, it is estimated that RM3 million grant has been granted to the researchers. Although there are various grants and the number of extensive researches, the result of the researches have not been published in any high impact journals such as Scopus and ISI (Institute for Scientific Information). The change of qualitative research to quantitative research that emphasizes the quantitative elements and its impact to the country should be intensified in the Faculty of Islamic Studies.